The multidimensional poverty index: Achievements, conceptual and empirical issues - Caroline Dotter; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2017)
The Multidimensional Poverty Index (MPI) has been an important contribution to the debate on national and international poverty measurement. With the creation of the global MPI, OHPI and UNDP have provided a household-level multidimensional poverty measure for over 100 developing countries that can usefully complement the widely used 1.25 a day income poverty indicator. Given its link to the concept of human development, it is an important element of the suite of human development indicators maintained and published by UNDP. Nonetheless, there are many open empirical questions and issues regarding the conceptual underpinning of the MPI that need to be discussed and carefully considered. This essay discusses issues with the dual cut-off method for poverty identification, and how inequality could be incorporated in this poverty measure. Moreover, the choice of headline indicator is debated. We also propose a number of changes regarding the empirical implementation. These include dropping the WHS as one of the data sources, dropping the BMI as a nutrition indicator, and changing the age ranges and cutoffs for the education and mortality indicators. Different approaches to deal with the large share of households where information on an MPI indicator is missing are also discussed. The empirical relevance of these changes are analysed using the Demographic and Health Surveys (DHS) for Armenia, Ethiopia, and India. We argue that these changes could pose improvements to the current formulation, but one may need to investigate them further and for a larger number of countries. In a final section, we briefly comment on the HDRO revisions to the MPI in the 2014 Human Development Report, which have been partly based on the recommendations made in this paper.
Keywords: 330